Gender as a moderator of the relation among social support functions and life satisfaction in older Malaysians - Kooshair, Hadi; Yahaya, Nurizan; Hamid, Tengku Aizan; Abu Samah, Asnarulkhadi (Taylor & Francis, 2014)
The aim of this study was to examine the moderating role of gender on relations among social support functions and life satisfaction in older Malaysians. The study sample was 1,800 older residents in a community; all were at least 60 years old. This study was a cross-sectional and corelational survey, and the data were collected by multistage stratified sampling. This study revealed that fewer social support functions, and therefore less life satisfaction, were available for females than for males. The results of moderated regression analyses demonstrated that gender interacted only on the relationship between positive social interaction support and tangible support with life satisfaction. Specifically, at a high tangible support level, females had lower life satisfaction when compared to a low tangible support level. There may be a need for new programs and services to provide other aspects of social support to older female adults to improve and maintain life satisfaction in later life.